Patients’ satisfaction and efficacy of modern conventional hearing aids: A comprehensive analysis of the self-reported user experiences in adult people - Daniele Portelli; Cosimo Galletti; Sabrina Loteta; Leonard Freni; Francesco Ciodaro; Angela Alibrandi; Giuseppe Alberti (Brazilian Journal of Otorhinolaryngology)
Objective: Hearing loss is a widespread condition that impacts the quality of life, affecting communication, social interactions, and cognitive functions. This study aimed to evaluate the subjective benefit and satisfaction of using hearing aids among patients since the adoption rate of hearing aids remains low. Methods: The study retrospectively analysed data from 133 patients with hearing aids, using the Abbreviated Profile of Hearing Aid Benefit (APHAB) and the Satisfaction with Amplification in Daily Life (SADL) questionnaires. Patients were divided into two groups based on this median age and sex for comparative analysis. The Mann Whitney test was applied with references to numerical parameters (APHAB and SADL) to assess differences between male vs female subjects and adults vs elderly. The Spearman correlation test was applied to assess the possible correlation between APHAB and SADL. A p-value lower than 0.05 was considered statistically significant. Results: Results indicated no significant gender differences in most APHAB and SADL subscales, except for the SADL “personal image” subscale, which showed lower scores for women (p =  0.023). Age-based comparison revealed no significant differences in APHAB scores; the SADL scores showed significant differences in the “positive effect” (p = 0.013), “negative features” (p = 0.005), and overall scores (p = 0.039), with lower satisfaction in older patients. Correlation analysis identified a positive relationship between the SADL “negative features” and APHAB “aversiveness” subscales (p = 0.042, correlation coefficient ρ = 0.176). Conclusions: The study highlights the importance of addressing subjective perceptions and aesthetic concerns in hearing aid adoption, emphasizing the need for personalized rehabilitation strategies to improve patient outcomes and satisfaction. Level of evidence: Level 3.